2009
DOI: 10.2147/vhrm.s6829
|View full text |Cite
|
Sign up to set email alerts
|

Patients with insulin-dependent diabetes or coronary heart disease following rehabilitation express serum fractalkine levels similar to those in healthy control subjects

Abstract: The chemokine and adhesion molecule fractalkine and its receptor CX3CR1 have emerged as interesting regulators in inflammation and related atherosclerosis. The pro-inflammatory status may be counteracted by appropriate treatment, such as in rehabilitation. We compared serum fractalkine concentrations of 46 patients with coronary heart disease (CHD) and 47 insulin-dependent diabetic patients (IDDM) following rehabilitation with those of 50 control subjects. Following rehabilitation serum fractalkine levels (477… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…However, in another study of CVD patients with and without T2DM or with and without MetS, no differences in circulating fractalkine concentration or expression of CX3CR1 were observed [ 32 ]. The lack of correlation between fractalkine levels and diabetes has also been reported by others [ 8 , 33 , 34 ]. Accumulating evidence, mainly from cell culture and animal studies, suggests that high glucose concentrations, similar to those seen in type 2 diabetes, promote the expression of fractalkine by smooth muscle cells and endothelial cells in vitro , which may then enhance monocyte adhesion and potentially promote atherogenesis [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, in another study of CVD patients with and without T2DM or with and without MetS, no differences in circulating fractalkine concentration or expression of CX3CR1 were observed [ 32 ]. The lack of correlation between fractalkine levels and diabetes has also been reported by others [ 8 , 33 , 34 ]. Accumulating evidence, mainly from cell culture and animal studies, suggests that high glucose concentrations, similar to those seen in type 2 diabetes, promote the expression of fractalkine by smooth muscle cells and endothelial cells in vitro , which may then enhance monocyte adhesion and potentially promote atherogenesis [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 73%
“…Fractalkine (CX3CL1), the only known member of the CX3C class of chemokines, is known to convey its signals through a single G-protein-coupled receptor, CX3CR1, thereby promoting leukocyte activation and survival [ 7 ]. Fractalkine expression has been detected in activated or stressed endothelial, smooth muscle cells, skeletal muscle, macrophages, neurons, hepatocytes [ 8 12 ], and adipocytes [ 13 ]. It is characterized as a structurally unique chemokine, with both membrane-bound and soluble forms that act, respectively, to promote cell-to-cell adhesion of circulating leukocyte or as a classical chemoattractant of monocytes and lymphocytes [ 9 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maegdefessel et al compared serum CX3CL1 concentrations among 46 patients with coronary heart disease, 47 insulindependent diabetic patients following rehabilitation and 50 control subjects. The authors demonstrated that following rehabilitation serum, CX3CL1 levels in coronary heart disease patients were similar to those in control subjects, whereas CX3CL1 levels were lower in insulin-dependent diabetic patients [36] . Li et al assessed the concentrations and mRNA expression levels of CCL2, CCL5, and CX3CL1 in 60 patients with acute myocardial infarction, 60 patients with unstable angina pectoris, 60 patients with stable angina pectoris and 40 patients without coronary heart disease.…”
Section: Wwwnaturecom/aps Apostolakis S Et Almentioning
confidence: 90%
“…Fractalkine, a chemokine that signals through a single known receptor (CX3CR1), has received considerable interest in relation to the contribution to atheroscleroisis. It has been described as a multidomain protein of exceptionally large size, i.e., 95 kDa, and is expressed on numerous cells, but more importantly, on activated endothelial, smooth muscle cells, and macrophages ( 8 , 9 ). In addition to its large size, another feature that is different from other members of the cytokine family is the presence of a transmembrane anchor, and as such, fractalkine is capable of mediating adhesion of cells expressing the G protein–coupled receptor CX3CR1.…”
mentioning
confidence: 99%